Relevance of the listener's motor system in recalling phrases enacted by the speaker - Ianì, Francesco; Bucciarelli, Monica (Memory (Hove), 2018)
Memory for series of action phrases improves in listeners when speakers accompany each phrase with congruent gestures compared to when speakers stay still. Studies reveal that the listeners' motor system, at encoding, plays a crucial role in this enactment effect. We present two experiments on gesture observation, which explored the role of the listeners' motor system at recall. The participants listened to the phrases uttered by a speaker in two conditions in each experiment. In the gesture condition, the speaker uttered the phrases with accompanying congruent gestures, and in the no-gesture condition, the speaker stayed still while uttering the phrases. The participants were then invited, in both conditions of the experiments, to perform a motor task while recalling the phrases proffered by the speaker. The results revealed that the advantage of observing gestures on memory disappears if the listeners move at recall arms and hands (same motor effectors moved by the speaker, Experiment 1a), but not when the listeners move legs and feet (different motor effectors from those moved by the speaker, Experiment 1b). The results suggest that the listeners' motor system is involved not only during the encoding of action phrases uttered by a speaker but also when recalling these phrases during retrieval.